Characteristics of Industry 4.0 Digital Technologies that have supported the Circular Economy (Research, Society and Development, 2021)
History has taken some leaps from time to time, when the subject is evolution, with changes in organizational aspects related to production systems, administrative processes, planning, mission definition and values ​​that guide good administrative practices, to meet society's wishes. There are many concepts and theories that characterize such changes, and they vary according to the reality that is lived at the time of their definitions. Nowadays, much has been said about Industry 4.0 and Circular Economy – EC, and their respective importance for achieving a development based on the triple bottom line – TBL, which seeks the best balance between economic, social, and environmental factors. This study aims to highlight part of the works that have explored such knowledge, from the perspective of the possible contributions that Industry 4.0 is offering for an effective implementation of CE within organizations. Through an integrative review, the research was carried out to identify these studies, based on Bardin's (1977) content analysis technique, with success in the preparation of a collection of works found in the scientific environment, which will certainly guide any related research. to this theme. The results point to an increasing attention to technological issues and their important integration with sustainable development, confirming the perception of the constant updating of business models and management theories, in tune with the current reality.